Measurement of the cosmic ray spectrum above 4×10^18 eV using inclined events detected with the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Ahn, E. J.; Al Samarai, I; Allekotte, Ingomar; Almela, Daniel Alejandro; Asorey, Hernán Gonzalo; Ave, M.; Avila, G.; Bertou, Xavier Pierre Louis; Contreras, F.; et al. (IOP Publishing, 2014)
Fil: Aab, A.. Universität Siegen; Alemania